2018
DOI: 10.1016/j.rpor.2018.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Intensity-modulated radiation therapy and volumetric modulated arc therapy versus conventional conformal techniques at high energy: Dose assessment and impact on second primary cancer in the out-of-field region

Abstract: The aim of this work was to estimate peripheral neutron and photon doses associated with the conventional 3D conformal radiotherapy techniques in comparison to modern ones such as Intensity modulated radiation therapy and volumetric modulated arc therapy. Assessment in terms of second cancer incidence ought to peripheral doses was also considered. For that, a dosimetric methodology proposed by the authors has been applied beyond the region where there is no CT information and, thus, treatment planning systems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…16 Other authors have published on out-offield dose from IMRT. 17,18 Vassiliev et al compared flattened and FFF beam out-of-field dose for 6 MV on a Varian 21EX machine using an ion chamber and a water phantom. 19 Kragl et al compared 6X and 6X-FFF for Elekta Precise linac using a farmer ion chamber, TLD rods, and radiochromic films for SBRT and IMRT plans.…”
Section: Ramsay Et Al Reported Out-of-field Data For Tomotherapy and Amentioning
confidence: 99%
See 1 more Smart Citation
“…16 Other authors have published on out-offield dose from IMRT. 17,18 Vassiliev et al compared flattened and FFF beam out-of-field dose for 6 MV on a Varian 21EX machine using an ion chamber and a water phantom. 19 Kragl et al compared 6X and 6X-FFF for Elekta Precise linac using a farmer ion chamber, TLD rods, and radiochromic films for SBRT and IMRT plans.…”
Section: Ramsay Et Al Reported Out-of-field Data For Tomotherapy and Amentioning
confidence: 99%
“…compared step and shoot IMRT with volumetric modulated arc therapy (VMAT) for a Siemens Primus accelerator using the Rando phantom with TLDs . Other authors have published on out‐of‐field dose from IMRT . Vassiliev et al.…”
Section: Introductionmentioning
confidence: 99%
“…Sánchez-Nieto et al [ 23 ] stated that technology advancements such as IMRT and VMAT were liable for an increase in doses received to out-of-field OARs. Fortunately, such a dose increase at a distance is greatly compensated by a significant reduction in the areas getting high doses.…”
Section: Discussionmentioning
confidence: 99%
“…[ 12 18 19 20 21 22 ] Several authors have measured doses of in-field and out-of-field organs in physical phantoms with passive detectors and compared their results with the TPS results. [ 8 12 21 22 23 24 25 ] All the investigators reported that the TPS cannot calculate the out-of-field dose accurately and the gold standard method to estimate this dose is MC simulation based on a patient’s DICOM data or using computational phantom. [ 12 17 26 27 28 29 ] Bednarz et al .,[ 26 ] Joosten et al .,[ 16 ] Berris et al .,[ 27 ] and Wang and Ding (2014)[ 30 ] evaluated the out-of-field dose calculated by different TPS and used the MC simulation to estimate the uncertainties of calculated organ doses.…”
Section: Introductionmentioning
confidence: 99%